DINAMIKA TEMPORAL DAN SPASIAL FOSFAT(PO4-P) DAN NITRAT (NO3-N) SEBAGAI INDIKATOR KESUBURAN PERAIRAN DI TELUK JAKARTA - Amanah Zakiah; Yonvitner; Ario Damar (Coastal and Ocean Journal (COJ), 2023)
Jakarta Bay is located on the north coast of Java Island and is the mouth of 13 major rivers in Jakarta, Bogor, Depok, Tangerang and Bekasi. Various activities that involve the use of waters, both bays and rivers, can cause a decrease in water quality and nutrient enrichment. One result of nutrient enrichment is an increase in nutrients such as phosphate and nitrate. This study aims to determine the pattern of spatial distribution of phosphate and nitrate concentrations as indicators of water fertility in Jakarta Bay. Water quality monitoring was carried out from 2012-2019 from 23 observation stations. The determination of 23 stations is based on the representation of the Jakarta Bay area into the coastal zone and the bay zone. Water fertility status based on phosphate nutrients is classified as mesotrophic with a spatial distribution pattern that is higher around the coast and lower as it approaches the mouth of the bay. Meanwhile, based on nutrient nitrate, it is classified as oligotrophic with a distribution that tends to be high on the beach and low near the mouth of the bay. Temporally, there is a significant difference in the concentration of phosphate and nitrate.